Evaluation Of Real-Time PCR For Early Diagnosis of Acute Respiratory Infections Among Pediatric Population at A Tertiary Care Setting - Sharma, Robin; K Rawat, Sumit; Kushwah, Sapna (Journal of Neonatal Surgery, 2025)
Respiratory infections are triggered by a variety of viruses, and there is a scarcity of information regarding viral coexistence, comparative symptoms, and overall burden of illness. This observational study was conducted to identify the etiological agents responsible for acute respiratory tract infections (ARI) in children under five years of age using the TRUPCR multiplex real-time respiratory pathogen panel. Samples were collected from pediatric patients with respiratory infections admitted to the Department of Pediatrics at Bundelkhand Medical College in Sagar, Madhya Pradesh, between June 2023 and January 2025. In total, 417 samples were subjected to real-time PCR analysis. RT-PCR detected 332 of 417 positive samples, resulting in an overall positivity rate of 79.6%. Family history of similar illnesses, breastfeeding, and nutritional status were significantly associated with acute respiratory infections.The highest prevalence of ARI (51.55%) was observed in children aged 1–12 months. The most common respiratory infections were noted in the 1 to 5 year age group (44.7%). The human respiratory syncytial virus (hRSV) was the most frequently identified virus (35.76%), followed by human rhinovirus (hRV) (27.81%), human adenovirus (hAdV) (6.29%), and influenza B virus (Inf B) (3.6%). No significant differences were noted in clinical presentation; however, fever, cough, breathlessness, and stridor were significantly associated with viral respiratory infections. These results enhance our understanding of viral etiology and distribution, which can improve the management and treatment of respiratory infections. Nevertheless, for a more comprehensive clinicopathological correlation, further studies should include a complete evaluation of all etiological agents, the clinical profiles of patients, and treatment outcomes. Therefore, multiplex real-time PCR may play a crucial role in the rapid and precise diagnosis of respiratory viruses, potentially improving patient outcome.